Inside Cover: Superior Ion‐Conducting Hybrid Solid Electrolyte for All‐Solid‐State Batteries (ChemSusChem 4/2015). Issue 4 (11th February 2015) - Kim, Jae‐Kwang; Scheers, Johan; Park, Tae Joo; Kim, Youngsik
<x xml:space="preserve">Abstract</x> The Inside Cover picture shows a hybrid solid electrolyte, which consists of LiTFSI salt, Py14TFSI ionic liquid, and TiO2 nanoparticles. The hybrid solid electrolyte prepared by a facile method has high room temperature ionic conductivity, excellent thermal stability, and low interface resistance with good contact. Moreover, the lithium transference number is increased by the scavenging effect of the nano‐TiO2 particles. With the hybrid solid electrolyte, the pouch‐type solid‐state battery allows high initial discharge capacity of 150 mAh g−1 at room temperature, and even at 1 C, the reversible capacity is as high as 106 mAh g−1. More details can be found in the Full Paper by Kim et al. on page 636 (DOI: 10.1002/cssc.201402969).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>